Covid19 Impact on Information Channels Choosing Preference During The Self-Study of Teachers in The Gender Context - Radim ŠTĚPÁNEK; Veronika ŠVRČINOVÁ; Svatopluk SLOVÁK; Pavel DOSTÁL (Communications of International Proceedings, 2020)
This article is focused on the analysis of information channels choosing preference during the self-study of teachers in the gender context for the decisive period from March to June 2020. Schools were closed worldwide in this period with the emphasis on communication with pupils via electronic platforms on the internet. Teachers were assimilated to completely new roles, within one week they had to adapt to this arisen situation and change the education in the sense of realised digital competence. The goal of the article is to find the scale of preferred information channels during the self-study of teachers and to compare the difference in preparations at men and women teachers in the three-month period mentioned above. We also wanted to know how the preference was changing according to the extent of the school residence where the online lessons were realised.
Keywords: COVID19; distant education; evaluation of teachers; pedagogy; self-study preference of teachers.